Kepatuhan Wajib Pajak dan Tax Law Enforcement Sebelum dan Sesudah Penerapan Laporan Keuangan XBRL (Studi Empiris Terhadap Perusahaan Terdaftar di Bursa Efek Indonesia Tahun 2015-2018) - Amalia, Nadya Rizki; Kustiawan, Memen; Adiprawira, Ida Farida; Widarsono, Agus; Yuniarti, Rozmita Dewi (Universitas Pendidikan Indonesia, 2021)
This study aims to see differences in taxpayer compliance and tax law enforcement before and after the implementation of XBRL financial report. This research is a quantitative descriptive study. The sample in this study was manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018 using the purposive sampling method. The analysis technique in this study uses the Mann-Whitney Difference Test. The results of the study obtained that there was no difference between taxpayer compliance before and after the implementation of XBRL financial report. There is a difference between tax law enforcement before and after the implementation of XBRL financial statements.